Answer:
Simplifying
3x + -5 = 6x + -13
Reorder the terms:
-5 + 3x = 6x + -13
Reorder the terms:
-5 + 3x = -13 + 6x
Solving
-5 + 3x = -13 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
-5 + 3x + -6x = -13 + 6x + -6x
Combine like terms: 3x + -6x = -3x
-5 + -3x = -13 + 6x + -6x
Combine like terms: 6x + -6x = 0
-5 + -3x = -13 + 0
-5 + -3x = -13
Add '5' to each side of the equation.
-5 + 5 + -3x = -13 + 5
Combine like terms: -5 + 5 = 0
0 + -3x = -13 + 5
-3x = -13 + 5
Combine like terms: -13 + 5 = -8
-3x = -8
Divide each side by '-3'.
x = 2.666666667
Simplifying
x = 2.666666667
Explanation: